Black-White Differences in Wealth and Asset Composition - Blau, Francine D.; Graham, John W. (Quarterly Journal of Economics, 1990)
Using data from the 1976 and 1978 National Longitudinal. Surveys of young men and young women, this study examines racial differences in the magnitude and composition of wealth and the reasons for them. On average, young black families hold 18 percent of the wealth of young white families, and hold their wealth in proportionately different forms. Even after controlling for racial differences in income and other demographic factors, as much as three-quarters of the wealth gap remains unexplained. We speculate on the causes for this, concluding that racial differences in intergenerational transfers most likely play an important role.